Agricultural transition in Russia, Central Asia, and Eastern Europe: Ten lessons for Venezuela - Brooks, Karen (International Food Policy Research Institute, 2020)
Thirty years have elapsed since the fall of communist governments in Eastern Europe and the Soviet Union. The collapse of political structures took with it regimes of highly administered management of agri-food systems. The shift from state management to markets has been generally known as the agricultural transition. The term is most frequently used in reference to the former Soviet Union and Eastern Europe, but key features of a move from dominant state intervention to greater reliance on markets characterized reforms in China after 1978, Vietnam in 1986 and thereafter, and many countries in Africa south of the Sahara during the years of structural adjustment in the 1990s. The policy reforms that constitute an agricultural transition are intrinsically difficult and made even more so when undertaken under conditions of crisis-induced chaos. Lessons from countries that have undergone the process might be of use, either as guidance or cautionary notes, to leaders and civil society groups in countries such as Venezuela that may be embarking on a transition or swept into one by circumstance. The paragraphs below attempt to summarize lessons from the early transition in Russia, Central Asia, and Eastern Europe in the 1990s.